Digital Financial Services-A Financial Inclusion Enabler: A Case Study of Zenith Bank Ghana Limited - Berkoh, D.B.A. (University Of Ghana, 2019)
There is an increased growth of the use digital financial services in the world. Many banks, financial institutions, savings and loans companies are establishing and implementing the use of these services to bridge financial inclusion. A study was conducted at Zenith Bank Ghana Limited to see the benefit of digital financial services among their clients and its contribution to financial inclusion. This study was done to determine the relationship between financial inclusion and digital financial services. It sought to quantitatively test the notion that mobile money, the use of ATM‟s and other E-services in most cases leads to financial inclusion. The study used primary data through the use of questionnaires. Using Regression analysis, the study determined how variables such as ATM‟s and E-banking services aside MOMO also affected financial inclusion. The findings of the study showed that there was a positive relationship between digital financial services (mobile money, ATM‟s, E-banking services) and financial inclusion. One suggestion for further studies recommends that banks should pursue more synergistic operating models that facilitate information and experience sharing in order to develop a wider range of bank services. A major limitation however was time constraint used to conduct this research.
MSc. Development Finance
Keywords: Financial Inclusion; Mobile Technology-Based Payment; Digital Payment System; Mobile Money; Zenith Bank Ghana Limited